W. Paul Strassmann. Technological change and economic development : the manufacturing experience of Mexico and Puerto Rico. Ithaca, Nueva York : Cornell University Press, 1968. 353 p. - Solís M., Leopoldo (Estudios Demográficos y Urbanos, 1969)
W. PAUL STRASSMANN, TechnoLogical Charnge. and Economic Development: the Manufiacturing Experience of Mexico and Puerto Rico. Ithaca, Nueva York, Cornell University Press, 1968.